1993
DOI: 10.1128/aac.37.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Trichophyton mentagrophytes activity and percutaneous permeation of butenafine in guinea pigs

Abstract: We examined anti-Trichophyton mentagrophytes activity, cutaneous penetration, and skin localization of mentagrophytes KD-04 were 0.025 and 0.39 ag/ml, respectively. (iii) When 0.2 ml of a 1% 14C-butenafine solution was applied for 23 h/day for 7 days, high radioactivity corresponding to 250 to 500 ,ig of butenafine per g of skin in the epidermis, including the horny layer, was observed. (iv) Butenafine penetrates through transepidermal and transfollicular routes. The excellent therapeutic efficacy of butenafin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…It has been reported that various antifungal agents developed recently, including neticonazole, lanoconazole, butenafine, amorolfine, and terbinafine, exhibit prolonged cutaneous retention times (2,7,25,29,33) and achieve concentrations far above the MICs for most dermatophytes in the horny layer when they are applied to the skin (5,22,34). However, it looks likely that these antifungal agents mostly exist in an inactive form in the skin tissues because several studies have demonstrated that their in vitro activities were markedly lower in the presence of keratin (1,21,30) or serum (6,8,14), probably through drug-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that various antifungal agents developed recently, including neticonazole, lanoconazole, butenafine, amorolfine, and terbinafine, exhibit prolonged cutaneous retention times (2,7,25,29,33) and achieve concentrations far above the MICs for most dermatophytes in the horny layer when they are applied to the skin (5,22,34). However, it looks likely that these antifungal agents mostly exist in an inactive form in the skin tissues because several studies have demonstrated that their in vitro activities were markedly lower in the presence of keratin (1,21,30) or serum (6,8,14), probably through drug-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an imidazole (lanoconazole) (20) and three classes of antifungal compounds, a benzylamine (butenafine) (17), an allylamine (terbinafine) (27), and a morpholine (amorolfine) (32), have been successfully developed and introduced into clinical use. These newer drugs are more highly active than the former imidazoles against dermatophytes in vitro (17,20,27,32) and in vivo in guinea pig models of dermatophytosis (2,3,4,5,25,26,29,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal drugs such as lanoconazole, butenafine, terbinafine, and amorolfine developed in recent years have potent in vitro antidermatophyte activity (11,14,18,28) in the horny layer and nails at high levels when topically applied (1,15,19,29). In our previous study with a guinea pig tinea pedis model (26), we demonstrated that the therapeutic efficacy of lanoconazole was not correctly assessed by the conventional culture method because of a carryover of the drug remaining in the treated skin tissues to the culture media for detecting fungi.…”
Section: Discussionmentioning
confidence: 99%
“…KP-103, amorolfine, or terbinafine was dissolved in a mixture of polyethylene glycol 400-ethanol (75:25, vol/vol) (1,17,(24)(25)(26) at 1% for topical application. Terbinafine hydrochloride tablets (Lamisil) were purchased from Novartis Pharma KK and suspended in coconut oil with a mortar, and the suspension was dispensed into capsules for oral administration.…”
mentioning
confidence: 99%